Establishment of MAGEC2‐knockout cells and functional investigation of MAGEC2 in tumor cells. Issue 12 (25th November 2016) - Wang, Jingjing; Song, Xiao; Guo, Chengli; Wang, Ying; Yin, Yanhui
Abstract : Cancer/testis antigen MAGEC2, a member of the type I melanoma‐associated antigen family, is expressed in a wide variety of cancer types but not in normal somatic cells. MAGEC2 has long been recognized as a tumor‐specific target, however, its functions remain largely unknown. In this study, we established MAGEC2‐knockout A375 melanoma cell lines using the CRISPR/Cas9 system. Seven clonal cell lines were generated by using four single guide RNAs targeting the coding region of the MAGEC2 gene, which produced indels that abolished MAGEC2 protein expression. To identify the differentially expressed protein profiles associated with MAGEC2 loss, isobaric tag for relative quantitation‐based comparative proteomics experiments were carried out on the MAGEC2‐knockcout and control A375 cells. Mining of the proteomics data identified a total 224 (61.6% upregulated and 38.4% downregulated) proteins to be significantly altered in expression level in MAGEC2‐knockcout cells. Ingenuity Pathway Analysis indicated that the significantly altered proteins were involved in critical neoplasia‐related biological functions such as cell death, proliferation, and movement. Gene ontology analysis identified "apoptosis signaling" as the top‐most upregulated pathway associated with MAGEC2 loss. We showed that knockout or knockdown of the MAGEC2 gene sensitized melanoma cells to tumor necrosis factor‐α‐induced apoptosis. Interestingly, actin‐based motility by Rho and RhoA signaling, known to promote cell migration, were also identified as the top downregulated pathways in MAGEC2‐knockout A375 cells. In short, our study provides a suitable cell model for exploring the biological functions of MAGEC2 in malignant cells, and sheds light on the molecular pathway by which MAGEC2 promotes tumor development. Abstract : We established MAGEC2‐knockout A375 melanoma cell lines using the CRISPR/Cas9 system, and subsequently carried out iTRAQ based comparative proteomics analysis to identify the differentially expressed protein profiles associated with MAGEC2 loss. The differentially expressed proteome was evaluated using the Ingenuity Pathways Analysis software, which revealed the molecular pathways that MAGEC2 may be involved in tumorigenesis and cancer development.